2023
DOI: 10.1186/s41747-023-00353-w
|View full text |Cite
|
Sign up to set email alerts
|

Bone biopsies guided by augmented reality: a pilot study

Abstract: Purpose To test the technical feasibility of an augmented reality (AR) navigation system to guide bone biopsies. Methods We enrolled patients subjected to percutaneous computed tomography (CT)-guided bone biopsy using a novel AR navigation system. Data from prospectively enrolled patients (AR group) were compared with data obtained retrospectively from previous standard CT-guided bone biopsies (control group). We evaluated the following: procedure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Technical success was defined as the ability to complete the procedure as initially planned [ 17 , 18 ] to reach the disc. Technical efficacy was based O 2 /O 3 intradiscal diffusion adequacy, as demonstrated by the last CT scan.…”
Section: Methodsmentioning
confidence: 99%
“…Technical success was defined as the ability to complete the procedure as initially planned [ 17 , 18 ] to reach the disc. Technical efficacy was based O 2 /O 3 intradiscal diffusion adequacy, as demonstrated by the last CT scan.…”
Section: Methodsmentioning
confidence: 99%
“…Solbiati et al [ 64 ] reported the first in vivo study of an AR system for the guidance of percutaneous interventional oncology procedures. Recently, Albano et al [ 65 ] performed bone biopsies guided by AR in eight patients with 100% technical success.…”
Section: Ultrasoundmentioning
confidence: 99%
“…By using AR goggles, the physician can very rapidly see the superimposed 3D reconstruction of organs and lesions on the patient in the correct location with very high precision. Moreover, the fiducials placed on the needle show when the needle reaches the target lesion with high accuracy [ 19 , 20 , 21 ]. Improvements were reported for depth perception and understanding of spatial anatomic relationships [ 22 ].…”
Section: Basics Of Navigation and Robotic Systemsmentioning
confidence: 99%
“…The EM field is incompatible with MRI [11,13,35], and large metallic objects may decrease the localization accuracy. fiducials placed on the needle show when the needle reaches the target lesion with high accuracy [19][20][21]. Improvements were reported for depth perception and understanding of spatial anatomic relationships [22].…”
Section: Basics Of Navigation and Robotic Systemsmentioning
confidence: 99%
See 1 more Smart Citation